Bangladesh : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2005)
This paper reviews Bangladesh's National Strategy for Accelerated Poverty Reduction (NSAPR). The main goal of Bangladesh's Poverty Reduction Strategy is based on a vision for poverty reduction formed on the basis of the understanding of key issues of the present state of the economy. To fulfill the vision of poverty reduction, four strategic blocks are identified. These four blocks are enhancing pro-poor growth, boosting critical sectors for pro-poor economic growth, devising effective safety nets and targeted programs, and finally ensuring social development.